2018
DOI: 10.1002/cam4.1583
|View full text |Cite
|
Sign up to set email alerts
|

ATPR‐induced G0/G1 phase arrest in gastric cancer cells by regulating the binding of 14‐3‐3ε and filamin A

Abstract: Abstract4‐amino‐2‐trifluoromethyl‐phenyl retinate (ATPR) was able to induce the G0/G1 phase arrest in gastric cancer SGC‐7901 cells by downregulating 14‐3‐3ε. However, the mechanisms underlying this effect have not been fully elucidated. Because 14‐3‐3ε functions as a molecular chaperone on cell cycle regulation, the interaction between 14‐3‐3ε and the target proteins is worth an in‐depth study. In this study, the use of targeting proteomics identified 352 14‐3‐3ε‐binding proteins in SGC‐7901 cells. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…14-3-3 proteins are found to be important in both cancer- and age-related neurodegenerative disease [ 40 ], which can directly interact with yki [ 17 ], an important cancer factor in the Hippo pathway [ 19 , 40 ]. Previous studies indicated that 14-3-3ε is involved in gastric cancer and colorectal cancer [ 41 , 42 , 43 , 44 , 45 , 46 ], and disrupted sleep is a risk factor that contributes to cancer [ 47 ]. Many current papers showed a link between molecules upregulated in cancer patients and selected sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14-3-3 proteins are found to be important in both cancer- and age-related neurodegenerative disease [ 40 ], which can directly interact with yki [ 17 ], an important cancer factor in the Hippo pathway [ 19 , 40 ]. Previous studies indicated that 14-3-3ε is involved in gastric cancer and colorectal cancer [ 41 , 42 , 43 , 44 , 45 , 46 ], and disrupted sleep is a risk factor that contributes to cancer [ 47 ]. Many current papers showed a link between molecules upregulated in cancer patients and selected sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…In this current study, we found that 14-3-3ε, controlled by Clock, regulates sleep through pathways of both the 14-3-3ε/Ubx/PDF and neurotransmitters. In addition, there are previous reports that 14-3-3ε is also related to cancers [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ], indicating that 14-3-3ε is a multifunctional gene in Drosophila regulating different physiological activities. Currently, the direct relationship between cancer and sleep is still unclear, which need to be carefully designed for systematical investigation in future.…”
Section: Discussionmentioning
confidence: 99%